Cortisol levels associated with mortality in children with critical illness: a systematic review - Restu Triwulandani Tolibin; Septin Widiretnani; Annang Giri Moelyo (Paediatrica Indonesiana, 2023)
Background Critically ill patients, including those with sepsis, have increased cortisol levels due to activation of the hypothalamic-pituitary-adrenal (HPA) axis or critical illness-related corticosteroid insufficiency (CIRCI).